Present situation of quality assessment of the Dentistry services in Cuba - José Luis Capote Femenías; Amalia Peña Rosell (Medisur)
Assessing the quality of health services is a complex task, due to the multidimensional character of its definition, diversity of the theoretical approaches and component variability of each specialty and service. This paper is aimed at presenting the characteristics of quality assessment in Dentistry services in Cuba at present. It was carried out a review of documentary and published studies in the last ten years. At the beginning antecedents and health services quality approaches are highlighted; then assessment methods and programs are presented, so as quality management in Cuba. The assessment is carried out by means of supervisions and audits to the services with particular interest in indicators statistics. This a fundamental element in the quality continue improvement program in Dental services and the satisfaction of providers, including annex II of the National Program of Dental Care to the population. Various sources identify quality problems in Dentistry services, which should be considered from the academic and administrative point of view. It is concluded that assessing dental services in Cuba, needs an updating or a methodological redesign.